Serious infections in patients with VEXAS syndrome: data from the French VEXAS registry - de Valence, Benjamin; Delaune, Marion; Nguyen, Yann; Jachiet, Vincent; Heiblig, Mael; Jean, Alexis; Riescher Tuczkiewicz, Stanislas; Henneton, Pierrick; Guilpain, Philippe; Schleinitz, Nicolas; Le Guenno, Guillaume; Lobbes, Hervé; et al. (Annals of the rheumatic diseases, 2024)
IntroductionVacuoles, E1 enzyme, X-linked, autoinflammatory, somatic (VEXAS) syndrome is an acquired autoinflammatory monogenic disease with a poor prognosis whose determinants are not well understood. We aimed to describe serious infectious complications and their potential risk factors.MethodsRetrospective multicentre study including patients with VEXAS syndrome from the French VEXAS Registry. Episodes of serious infections were described, and their risk factors were analysed using multivariable Cox proportional hazards models.ResultsSeventy-four patients with 133 serious infections were included. The most common sites of infection were lung (59%), skin (10%) and urinary tract (9%). Microbiological confirmation was obtained in 76%: 52% bacterial, 30% viral, 15% fungal and 3% mycobacterial. Among the pulmonary infections, the main pathogens were SARS-CoV-2 (28%), Legionella pneumophila (21%) and Pneumocystis jirovecii (19%). Sixteen per cent of severe infections occurred without any immunosuppressive treatment and with a daily glucocorticoid dose ≤10 mg. In multivariate analysis, age >75 years (HR (95% CI) 1.81 (1.02 to 3.24)), p.Met41Val mutation (2.29 (1.10 to 5.10)) and arthralgia (2.14 (1.18 to 3.52)) were associated with the risk of serious infections. JAK inhibitors were most associated with serious infections (3.84 (1.89 to 7.81)) compared with biologics and azacitidine. After a median follow-up of 4.4 (2.5–7.7) years, 27 (36%) patients died, including 15 (56%) due to serious infections.ConclusionVEXAS syndrome is associated with a high incidence of serious infections, especially in older patients carrying the p.Met41Val mutation and treated with JAK inhibitors. The high frequency of atypical infections, especially in patients without treatment, may indicate an intrinsic immunodeficiency.